Scientiﬁc discussion on the essence of state ﬁnancial regulation of socio-economic inequality in modern conditions - M. L. Dorofeev (Управление)
The article is devoted to the analysis of contemporary problems and peculiarities of regulating socio-economic inequality during the crisis and describes the ﬁnancial crises’ impact mechanism on the state ﬁnancial regulation evolution of economic inequality.In times of economic crises developed countries make unconditional distributions of money transfers to households to stimulate demand. New liquidity is distributed across the world economy, launching inﬂationary processes against the backdrop of signiﬁcant problems with the supply of raw materials and materials due to the consequences of the COVID-19 pandemic. Public interest to the problem of growing socio-economic inequality is increasing along with the rise in the number of dollar millionaires and the ﬁnancial assets prices. In many ways, this phenomenon is associated with the ﬁnancial regulation speciﬁcs of the economy during times of crises.As a result of the study, the speciﬁcs and paradoxes of modern state ﬁnancial regulation of economic inequality during times of crises have been substantiated, recommendations for state ﬁnancial regulation of socio-economic inequality during the crisis have been formulated. Regulators should pay particular attention to the top 10 % of the population, for whom there are now many opportunities for tax optimisation and avoidance, with the result that even theoretically effective progressive tax systems do not work properly in practice. Developed countries should promote international tax cooperation to solve this problem, and developing countries should focus on improving their progressive tax systems.